TQManager : a practical guide for managing in a total quality organization - Schmidt, Warren H. 4 0 16; 1935- Finnigan, Jerome P.; 5 (San Fransisco, California : Jossey-Bass Publishers, 1993)
Provides managers with information on total quality management, identifies where improvement is needed, and how to create a plan of action.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Total quality management. -- 20; 20; 2